ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT MAYORA INDAH, Tbk MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) PERIODE 2012-2018 - Rafiqoh Rafiqoh; Eko Adi Widyanto; Rifka Maulida (Politeknik Negeri Samarinda, 2019)
The Objectives of this research are to determine the financial performance of PT Mayora Indah, Tbk by using the Economic Value Added (EVA) method for the 2012-2018 period. The research method that I use is quantitative descriptive research by analyzing financial statements using quantitative data, namely the statement of financial position and the income statement of PT Mayora Indah, Tbk. The type of data used is secondary data obtained directly from the site www.idx.co.id, www.mayoraindah.co.id, www.finance.yahoo.com and www.bi.go.id. The analytical tool used is the Economic Value Added (EVA) method which consists of: Net Operating After Tax (NOPAT), Weight Average Cost of Capital (WACC), Total Capital Structure, Capital Costs and Economic Value Added (EVA). Based on the results of the analysis and discussion conducted at PT Mayora Indah, Tbk during the 2012-2018 study period using the EVA method, the results showed a positive EVA value. Keywords: Financial Performance, Economic Value Added (EVA)